Standardization of Ethanol Extract of Dioscorea alata L. Variety of Paoateno from Banggai Islands District, Central Sulawesi: Standarisasi Ekstrak Etanol Dioscorea alata L. Varietas Paoateno Asal Kabupaten Banggai Kepulauan Sulawesi Tengah - Ismail, Ihwan; Khumaidi, Akhmad; Putri, Ayu Dinawati; Primadia, Rizki; Syamsidi, Armini; Khaerati, Khildah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Standardizing herbal medicines is crucial for assessing their quality and effectiveness. Objectives: This study aims to determine non-specific and specific standardization parameters for medicinal plants. Non-specific parameters include drying shrinkage, water content, total ash content, acid insoluble ash content, total bacteria, total mold, and metal limits (Pb, Hg, and Cd). Specific parameters involve organoleptic examination, identification of chemical content in extracts, dissolved compounds in specific solvents, total flavonoid content, and qualitative testing of anthocyanin content in the extract. Materials and Methods: An experimental laboratory approach was employed to extract Dioscorea alata L using 96% ethanol, which was later concentrated through a rotary evaporator to obtain a viscous extract. Specific and non-specific parameters were determined using standardized techniques. Results: The extract yielded 3.32% of the initial substance. Drying shrinkage was 19.7769±1.2682%, and specific gravity was 0.6192±0.1476 gram/ml for 5% m/v and 0.5101±3.9591 gram/ml for 10% m/v. Ash content was 0.6793%, with acid insoluble ash content at 0.1895%. Heavy metal contamination for Hg was 0.47 ppm, but undetected for Pb & Cd). The total plate number was 27 x 103 colonies/g, and negative Escherichia coli contamination. The mold count was 39 x 101 colonies/g. Additional specific parameters included the organoleptic properties of the viscous extract (purple color, characteristic odor, and sweet taste), water-soluble compound content (15.63%), ethanol-soluble compound content (14.73%), and a flavonoid content of 76.669 mg EQ/100 mg. Conclusions: The ethanol extract of Dioscorea alata complies with the standard requirements established by the Food and Drug Supervisory Agency. It presents as a viscous extract with a distinct odor, purple-black color, and sweet taste. The extract contains alkaloids, flavonoids, saponins, tannins, steroids, and phenolic compounds, with a total flavonoid content of 76.669 mg. Furthermore, it tested positive for anthocyanins.